Prosedur Kredit Dan Pelayanan Nasabah Pt. Bank Rakyat Indonesia Kantor Cabang A. Rivai Palembang - Nesya Putri Alfian; Asih Kinanti; Suci Ramadani; R.M Rum Hendarmin; Lukita Tripermata (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
Banking is a business entity trusted by the public to collect and manage their savings. In banks, there are many types of transactions and activities provided for community services that called customers. PT Bank Rakyat Indonesia is the intended business entity to implement economic science and a form of community service through banking services. Implementing Merdeka Learning Campus Program at Bank Rakyat Indonesia Branch A. Rivai Palembang as a form of community service through banking services such as printing bank statements, unblocking pension customer accounts, managing Non-Tax State Revenue, People's Business Credit programs, and managing bank administration. The method of implementing the MBKM program follows procedures from the university and the bank, namely filing and cooperation agreement (MoU). The result of the implementation of MBKM is that the author gets an expansion in knowledge in the field of banking which can then be evaluated as an initial step in self-development and preparation for the world of work in the future.